Corporate social responsibility initiatives influence customer awareness and empowerment - Loureiro, S. M. C.; Lopes, J. (GAMMA-Global Marketing Conference-Bridging Asia and the World: Searching for Academic Excellence and Best Practice in Marketing and Management, 2018)
The traditional approaches on corporate social responsibility communication are revealing to be unable of raising awareness and increasing stakeholders’ empowerment, often failing to improve positive relationships with consumers. In this study, the digitally co-created CSR activities will be explored using a more general approach, which will also take into consideration these philanthropic activities, i.e. the activities where companies invite stakeholders to participate in the resolution of a social issue but without asking them to buy the brand’s products. Moreover, in the present study, interactivity and freedom of cause' choices are both believed to be two mechanisms that play a key role in generating more empowered stakeholders, with increased propensity for participating in co-created CSR initiatives. Therefore, it is important to analyse digitally co-created CSR activities since it may represent a major opportunity for organizations to add value and meaning to stakeholders (and even for society at large), where the two parties work together to solve a social issue.